2010
DOI: 10.1177/154193121005401920
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Human Factors: Children's Mental Models of Computers

Abstract: Two groups of first, third, and fifth grade children were interviewed about their mental models of computers. The first group was interviewed in 1999, and the second in 2009. In both data sets, children as young as 6 years of age generated well developed analogies for computers. However, the 2009 data showed that children are increasingly able to generate these analogies at a younger age. Further, the types of analogies generated differed as a function of time, with those interviewed in 1999 more likely to des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A person's mental model is unique to them, and may not actually be representative of how the system actually functions. Previous research has looked at the impact of time on children's mental models of computers, as well whether an adult's gender and trust in computers impacts the mental model he or she has of them (Oleson, Sims, Chin, Lum, & Sinatra, 2010; Sims, Chin, Durrance & Johnson, 2004).…”
Section: Mental Models and Analogy Generationmentioning
confidence: 98%
“…A person's mental model is unique to them, and may not actually be representative of how the system actually functions. Previous research has looked at the impact of time on children's mental models of computers, as well whether an adult's gender and trust in computers impacts the mental model he or she has of them (Oleson, Sims, Chin, Lum, & Sinatra, 2010; Sims, Chin, Durrance & Johnson, 2004).…”
Section: Mental Models and Analogy Generationmentioning
confidence: 98%
“…A comparison of children's attitudes in 1999 and again in 2009 found that children are able to conceptualise both technology and the concept of computers from as young as six years old, and that they can create these ideas at a younger age now compared to 1999. In 2009 children were more likely to describe entertainment, communication and game based activities when describing technology, whereas in 1999 descriptions were related to the physical nature of the computer itself [19].…”
Section: The Technology Experience For the Childmentioning
confidence: 99%
“…Furthermore, neither Bofferding (2014), Chinnapan (1998), as well as Greefrath et al (2020Greefrath et al ( , 2022 does not disclose and describe the process of accommodation of mental models during problem-solving. Whereas Oleson et al (2010), Piaget (1954), andvan Ments &Treur (2022) state that mental models experience an adaptation process through two forms, namely assimilation and accommodation, but according to Ifenthaler et al (2008) and van Ments and Treur (2022) mental models only experience accommodation processes. Nonetheless, neither Ifenthaler et al (2008) nor van Ments and Treur (2022) also do not describe how the process of mental accommodation is described when solving problems.…”
Section: Introductionmentioning
confidence: 99%